DETEKSI LEMBAR JAWABAN KOMPUTER MENGGUNAKAN OMR (OPTICAL MARK RECOGNITION) DI MTS NURUL IMAN - Moh Novi Hermawan; Maulidiansyah Maulidiansyah; Sudriyanto Sudriyanto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Conventional exams or manual exams were implemented decades ago and are still used today. This type of test uses a writing instrument as a test medium, namely the test is carried out in the form of general stationery such as paper, pencil, and pen, the questions and answers to the test are written by hand. One way to assess the success of the teaching process in schools is to carry out exams. In the implementation of the exam at MTS Nurul Iman, he used a computer answer sheet as an entry. Meanwhile, schools are required to have certain scanners that are expensive to correct computer answer sheets. Another alternative that can be done by schools is to manually correct computer answer sheets, but this makes a lot of time wasted, and can cause errors in correcting and slow work productivity. From the problems that have been described, to detect the computer answer sheet, a method is needed. Through this research, it is hoped that a method can be developed that automatically detects the answer choices on the computer answer sheet, so that more accurate and faster results are obtained. Based on the problems of this study, the researchers used the OMR (Optical Mark Recognition) method to detect computer answer sheets automatically. From the test results, it can be concluded that the accuracy of detection of computer answer sheets using OMR is 97%.